Student-Centred Approaches: Translating Theory into Practice by Science Teachers in Malawi Secondary Schools’ Context - Mpaso, Cedric Nthyolamwendo; Xuefu, Xu (Universitas Negeri Semarang, 2025)
For some time, student-centred approaches in secondary schools have been advocated for the teaching and learning of mathematics and science in Malawi. It, however, became formal for all subjects after the 2015 curriculum review. Adopting an outcome-based education (OBE) curriculum in secondary education necessitated its implementation through student-centred learning approaches. Since the formalization of the instructional strategy, not much is known about how science teachers effectively implement student-centred teaching in their lessons. This study aims to determine the extent of student-centred teaching implementation in science classrooms as teachers translate theory into practice. Secondary schools were randomly sampled in the Central West Education Division, and the school management identified the teachers to participate in the study. Data was collected through document analysis, lesson observation, and interviews. Seven different science lessons in Biology, Physics, and Chemistry, taught by seven different science teachers, were observed in various schools in Malawi. The study has found that implementing student-centred learning is still challenging due to teachers’ varied conceptualization of the construct, unavailability of adequate resources, and teacher capacity-related issues such as knowledge and skills. This affects attainment levels of the curriculum objectives, consequently challenging the achievement of national goals, as highlighted in Malawi Vision 2063, which is grounded in sustainable development goals in the long term.